2003
DOI: 10.1213/01.ane.0000081798.89853.e7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Psoas Compartment Block and Spinal and General Anesthesia for Outpatient Knee Arthroscopy

Abstract: Outpatient knee arthroscopy may be performed using a variety of anesthetic techniques. We report that spinal anesthesia and psoas compartment block are superior to general anesthesia when considering resource utilization, patient satisfaction, and postoperative analgesic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 18 publications
2
67
1
1
Order By: Relevance
“…22,23,24,25 The result is similar to our study result. Sansone and others in their study showed 82% patients undergoing ACL reconstruction getting sciatic femoral block bypassed post-anaesthetic care unit.…”
Section: Resultssupporting
confidence: 91%
“…22,23,24,25 The result is similar to our study result. Sansone and others in their study showed 82% patients undergoing ACL reconstruction getting sciatic femoral block bypassed post-anaesthetic care unit.…”
Section: Resultssupporting
confidence: 91%
“…Little is known about the factors that could favor epidural spread at the thoracic level. For psoas block, keeping the injection pressure below 15 psi and placing the side to be blocked dependent are two measures that have been proposed to decrease this phenomenon (Gadsden et al, 2008;Jankowski et al, 2003). In our study, we deliberately placed the side to be blocked up while keeping the injection pressure low so as to evaluate epidural spread of the solution in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(20), adequate anesthesia could not be provided by femoral sciatic block in one of 25 patients, however, in another study by Fanelli et al (23), this rate has been reported as 4% (21). The failure rate of spinal anesthesia with lowdose bupivacaine ranges between 3% and 6% (24). These findings have suggested that both methods have similar anesthetic efficacy in outpatient knee surgery and there is no difference in terms of success rate in practical terms.…”
Section: Discussionmentioning
confidence: 97%